(untitled) (The Planet, 2024)
Introduction: Breast cancer stands as the foremost cause of morbidity and mortality among females globally, including Bangladesh. Metastasis development is a crucial prognostic factor in invasive breast cancer, often requiring systemic treatment. The aberrant expression of adhesion-related antigens on tumor cells strongly indicates the tumor’s metastatic potential, leading to a poor prognosis for the patient. This study aimed to assess the expression of E-Cadherin and its association with histological prognostic parameters of breast carcinoma. Methods and materials: This cross-sectional study was conducted at the Department of Pathology, Dhaka Medical College, Dhaka, Bangladesh from March 2020 to February 2022. A total of 41 patients diagnosed with invasive breast carcinoma of no specific type were included in the study using convenient sampling. SPSS Version 23.0 was used for data analysis. Results: In this study, most patients exhibited E-Cadherin negativity, significantly associated with histological grading, increased tumor size (p = 0.024), more metastasized lymph nodes (p = 0.032), and triple-negative breast cancer (p = 0.011). Loss of E-Cadherin expression in both core needle biopsy and mastectomy samples showed a significant association with higher tumor grade (p = 0.009 and 0.028, respectively). Conclusion: Assessing E-Cadherin expression may be crucial in evaluating tumor aggressiveness and planning treatment modalities.